2014
DOI: 10.7603/s40706-014-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Workforce Supported Through ‘Transformational Leadership’ Ensures Higher Operational Responsiveness

Abstract: The study provides basis to measure ‘learning effectiveness’ through directional‘ leadership Management Options’ (i.e. Controlling Management, Passive Management and Transformational Leadership) in teams reflecting ‘Individual Differences’ to ensure organizational competitiveness. The study results confirmed that Transformational leadership provides strong basis for gaining and displaying exceedingly higher performance levels by even the ordinary team performers marked by ’‘Individual Differences’ phenomenon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A study has reported positive relationships between transformational leadership and its effects at the individual level and the corporate levels (Avolio, 1999, Kazmi & Kinnunen, 2012, Kazmi, Naaranoja & Takala, 2013. This fact further proves and supports the assessment that the transformational form of leadership has the ability to reveal the maximum levels of commitment, cohesion, motivation, trust as well as the performance in the new and more innovative organizational environments (Mengue,B., Auh.S., Shih.E 2007).…”
Section: Autocratic Leadership: No Focus On Consulting Others While Dmentioning
confidence: 68%
See 2 more Smart Citations
“…A study has reported positive relationships between transformational leadership and its effects at the individual level and the corporate levels (Avolio, 1999, Kazmi & Kinnunen, 2012, Kazmi, Naaranoja & Takala, 2013. This fact further proves and supports the assessment that the transformational form of leadership has the ability to reveal the maximum levels of commitment, cohesion, motivation, trust as well as the performance in the new and more innovative organizational environments (Mengue,B., Auh.S., Shih.E 2007).…”
Section: Autocratic Leadership: No Focus On Consulting Others While Dmentioning
confidence: 68%
“…In other words, the "Transactional leadership style" promotes the contingent reward and management-by-exception. However, contrary to the above, transformational leaders motivate followers to achieve performance beyond expectations by transforming followers' attitudes, beliefs, and values as opposed to simply gaining compliance (Bass,1985, Kazmi & Takala, 2011, Kazmi & Kinnunen, 2012, Kazmi, Naaranoja & Takala, 2013.…”
Section: Group Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In research literature, transformational leadership refers to the desirable characteristics of organization's leadership support practices. In our survey, this concept refers to an organization's capacity to offer its work teams with supportive leadership Avolio, 1992: Zaccaro, 1996;Kazmi, takala, 2011;Kazmi, Kinnunen, 2012;Kazmi, Naaranoja, Takala, 2013; environment for new product development idea generation. The selected indicators seek feedback to reveal organizational practices with reference to transformational leadership connected to new product development idea generation team potential.…”
Section: Arrangement Of the Construct Variables; Transformational Lea...mentioning
confidence: 99%